Effects of Oxyamylose and Polyacrylic Acid on Foot-and-Mouth Disease and Hog Cholera Virus Infections - Leunen, Joseph (1971)
Two interferon-inducing polycarboxylates were tested for antiviral activity on foot-and-mouth disease (FMD) virus infections in mice, guinea pigs, and swine. Polyacrylic acid, given intraperitoneally, had a protective effect on infection by FMD virus administered in the peritoneal cavity of mice and in the foot pad of guinea pigs. Chlorite-oxidized oxyamylose (COAM) was effective in mice at a dosage of 2 mg/kg. Swine were not protected against naturally transmitted FMD by 120 mg/kg of COAM nor by polyacrylic acid. Swine were not totally unresponsive to COAM since it delayed symptoms of hog cholera. Interferon was not detected in the serum of COAM-treated swine. With FMD virus, an example was found of activity of interferon inducers in experimental hosts and lack of activity in a natural host.